Students’ Perceptions about Role of Faculty and Administrative Staff in Business Education Service Quality Assessment - Maja Arslanagić-Kalajdžić; Selma Kadić-Maglajlić; Muris Čičić (Tržište, 2014)
This paper focuses on dimensions of the perceived service quality measurement for business schools. We propose an adapted SERVQUAL measure of expected and perceived quality, where employees at business schools are split into two groups: faculty and administrative staff, and assessed separately. This measure represents a tool for comparable service quality assessment at business schools. Empirical data were collected among undergraduate students in a developing economy. A total of 282 respondents were used to assess the overall fit of the proposed model and to test the differences between the expectations and the perceptions of service quality in a business school. The results support usability of the proposed adapted SERVQUAL measure. Therefore, the study contributes to the existing literature reporting the findings on service quality in an educational context.